2017
DOI: 10.1080/21513732.2017.1399929
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of biodiversity loss and restoration scenarios on tree-related ecosystem services

Abstract: In landscapes worldwide, trees in forests and agricultural lands have important ecological functions. Their loss may have important consequences for the delivery of ecosystem services (ES) to local communities, even if individual trees have low conservation values. This study explores the effect of land use and land use change on the provisioning of tree-related ES in a mixed Afromontane landscape in Ethiopia. First, we mapped the current distribution of treerelated ES using indicator ES, which represent the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Rare species can have unique function roles in ecosystems, and in some cases the provision of a service may be entirely dependent on presence of a rare species (Dee et al, 2019). For example, in a mixed Afromontane landscape in Ethiopia, Tekalign et al (2017) found that rare tree species have distinct traits that provide specific services, which could not be compensated by the remaining common species.…”
Section: Ecological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare species can have unique function roles in ecosystems, and in some cases the provision of a service may be entirely dependent on presence of a rare species (Dee et al, 2019). For example, in a mixed Afromontane landscape in Ethiopia, Tekalign et al (2017) found that rare tree species have distinct traits that provide specific services, which could not be compensated by the remaining common species.…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…Rare species can have unique function roles in ecosystems, and in some cases the provision of a service may be entirely dependent on presence of a rare species (Dee et al, 2019). For example, in a mixed Afromontane landscape in Ethiopia, Tekalign et al (2017) found that rare tree species have distinct traits that provide specific services, which could not be compensated by the remaining common species. Similarly, charismatic threatened tree species such as the Giant Redwoods ( Sequoiadendron giganteum ) of California have high value for provision of aesthetic and recreational services; such trees can also have iconic or spiritual value to people.…”
Section: What Are the Implications Of Tree Extinctions?mentioning
confidence: 99%
“…A forte ligação entre biodiversidade, funcionamento dos ecossistemas e seus serviços leva a supor que a restauração dos ecossistemas também restaurará os serviços prioritários afetados Tekalign et al, 2017). Embora essa suposição seja defensável para alguns serviços ecossistêmicos, como o abastecimento de água (Sonter et al, 2018), a relação entre a restauração da biodiversidade e os serviços ecossistêmicos não é diretamente proporcional e depende da categoria de serviços considerada (Benayas et al, 2009).…”
Section: Princípios E Critérios Aplicáveis à Compensação Por Perda E/...unclassified